Parent training for preschool ADHD in routine, specialist care: a randomized controlled trial - Lange, Anne-Mette; Daley, David; Frydenberg, Morten; Houman, Tine; Kristensen, Lene Juel; Rask, Charlotte; Sonuga-Barke, Edmund; Søndergaard-Baden, Signe; Udupi, Aparna; Thomsen, Per Hove (Elsiever, 2018)
Objective